2019
DOI: 10.1111/den.13353
|View full text |Cite
|
Sign up to set email alerts
|

Role of photodynamic therapy in the treatment of esophageal cancer

Abstract: Photodynamic therapy (PDT), a treatment of choice for cancer, induces a photochemical reaction, thereby eradicating tumor cells. This is achieved through the administration of a photosensitizer drug, which is activated with a laser after localization to the tumor mass, and is an approved curative endoscopic ablative treatment for superficial esophageal squamous cell carcinoma (ESCC) in Japan. PDT has been approved for dysplastic Barrett's esophagus and as a palliative treatment for patients with symptomatic ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 66 publications
0
71
0
Order By: Relevance
“…37 The largest study of palliative PDT for 215 affected patients reported improved dysphagia in 85%, achieving an average of 4.8 months of overall survival and a median of 2 months of dysphagia relief. 37,38 PDT using talaporfin sodium and diode laser has also been successfully used as a salvage treatment for local failure after chemotherapy or radiation therapy (CRT) for esophageal carcinoma. A prospective study found that complete remission was obtained in 19/25 patients (76%, 95% CI 55%-91%), with local failure limited to the submucosal layer.…”
Section: Gastrointestinal System Tumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…37 The largest study of palliative PDT for 215 affected patients reported improved dysphagia in 85%, achieving an average of 4.8 months of overall survival and a median of 2 months of dysphagia relief. 37,38 PDT using talaporfin sodium and diode laser has also been successfully used as a salvage treatment for local failure after chemotherapy or radiation therapy (CRT) for esophageal carcinoma. A prospective study found that complete remission was obtained in 19/25 patients (76%, 95% CI 55%-91%), with local failure limited to the submucosal layer.…”
Section: Gastrointestinal System Tumorsmentioning
confidence: 99%
“…As palliative treatment, stenting is still more commonly used for treatment of dysphagia in end‐stage esophageal cancer; however, PDT plays a large role in patients who cannot tolerate stents due to severe pain or post‐radiotherapy and has been shown to have a favorable survival outcome compared to other interventions when used initially . The largest study of palliative PDT for 215 affected patients reported improved dysphagia in 85%, achieving an average of 4.8 months of overall survival and a median of 2 months of dysphagia relief …”
Section: Efficacy For Solid Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…86 In addition, when recurrence was found after CRT, morbidity and mortality rates of patients who underwent salvage esophagectomy after CRT increased because of the effects of the radiation given to the mediastinum and the tissues used as conduits. 92,93 However, other recent studies have suggested a promising degree of efficacy of photodynamic therapy, 94 a much-less-invasive treatment option in Figure 1 Curability criteria for endoscopic resection (ER) and the rate of lymph node metastasis (LNM) in superficial esophageal squamous cell carcinoma (SESCC). ¶No additional treatment is recommended in the white area, no definite recommendation is proposed in the gray area, and additional treatment is recommended in the black area.…”
Section: Advantages and Disadvantages Of Additional Treatmentmentioning
confidence: 99%